Advances in Lipid and Metal Nanoparticles for Antimicrobial Peptide Delivery - Marcin Makowski; Ítala C. Silva; Constança Pais do Amaral; Sónia Gonçalves; Nuno C. Santos (Pharmaceutics, 2019)
Antimicrobial peptides (AMPs) have been described as excellent candidates to overcome antibiotic resistance. Frequently, AMPs exhibit a wide therapeutic window, with low cytotoxicity and broad-spectrum antimicrobial activity against a variety of pathogens. In addition, some AMPs are also able to modulate the immune response, decreasing potential harmful effects such as sepsis. Despite these benefits, only a few formulations have successfully reached clinics. A common flaw in the druggability of AMPs is their poor pharmacokinetics, common to several peptide drugs, as they may be degraded by a myriad of proteases inside the organism. The combination of AMPs with carrier nanoparticles to improve delivery may enhance their half-life, decreasing the dosage and thus, reducing production costs and eventual toxicity. Here, we present the most recent advances in lipid and metal nanodevices for AMP delivery, with a special focus on metal nanoparticles and liposome formulations.